THE J-CURVE HYPOTHESIS AND THE NIGERIAN OIL SECTOR: THE ARDL BOUNDS TESTING APPROACH - David Umoru; Matthew I. Eboreime (European Scientific Journal, ESJ, 2013)
We have in this paper attempted to shed empirical evidence on unresolved issues regarding the J-curve trade effect of real exchange rate depreciation with special focus on the Nigerian oil sector using the Bounds testing approach on time series data that spans over a 40-year period. Despite the well known argument that a real depreciation initially deteriorates the trade balance but through time, the trade balance improves such that the time path associated with the response of the trade balance generates a tilted J-curve, the present empirical evidence could not establish the classic J-curve exchange rate effect on the trade balance of the Nigerian oil sector. Indeed, the trade balance contemporaneously gains improvement in the short-run making it imperative for us to tag such an observation, the “inverted’ J-curve, a behaviour that took for granted, the predicted J-curve effect, and hence it is concluded that the standard J-curve hypothesis cannot be validated for the Nigerian oil sector. That Nigerian exports and imports are frequently denominated in foreign currency; the US dollar is a possible explanation for the contradicted J-curve effect.